2007
DOI: 10.1002/qua.21474
|View full text |Cite
|
Sign up to set email alerts
|

3D‐quantitative structure activity analysis and quantum chemical analysis of pyrido‐di‐indoles

Abstract: ABSTRACT:The computational analyses of pyrido-di-indoles have been performed with various methods such as quantum mechanical studies (AM1, PM3, and DFT) and 3D-QSAR analyses (CoMFA and CoMSIA). The electrophilicity index along with some other properties has been related with biological activities. Electrostatic field has been identified as an important descriptor from the 3D-QSAR analyses. The AM1 geometry and Gasteiger-Marsili charged base CoMFA (r predictive 2 ϭ 0.75) and CoMSIA (r predictive 2 ϭ 0.62) give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…PLS method [25,26] was used to linearly correlate these CoMFA and CoMSIA descriptors to the activity. The basic statistical setup was same as defined in our earlier works [10,22,27]. To have robustness and statistical confidence of the derived models, bootstrapping analysis used for 10 runs.…”
Section: Partial Least Square (Pls) Analysis and Validation Of Qsar Mmentioning
confidence: 99%
“…PLS method [25,26] was used to linearly correlate these CoMFA and CoMSIA descriptors to the activity. The basic statistical setup was same as defined in our earlier works [10,22,27]. To have robustness and statistical confidence of the derived models, bootstrapping analysis used for 10 runs.…”
Section: Partial Least Square (Pls) Analysis and Validation Of Qsar Mmentioning
confidence: 99%
“…In order to understand the factors affecting the inhibitory potency of these HIF-1 inhibitors, quantitative structure activity relationship (QSAR) studies were performed. Of the many available three-dimensional-quantitative structure-activity relationship (3D-QSAR) techniques (Pasha et al, 2007a(Pasha et al, , 2007b(Pasha et al, , 2007c(Pasha et al, , 2008. The pharmacophore-based alignment was performed by the PHASE program (Schrödinger, 2008a) in the Schrödinger package.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR techniques increase the probability of success and reduce the time and cost involved in the drug discovery process (Blair et al, 1977;Greco, et al, 1992). Various methods, such as QSAR based on physical and electronic properties, are used in practice (Pasha et al, 2008(Pasha et al, , 2007a(Pasha et al, , 2005aSingh et al, 2004a). Previously a number of QSAR studies on classic BDZ molecules have been reported (Greco et al, 1992;Gupta, 1995;Gupta et al, 1996;HadjipavlouLitina et al, 2004).…”
Section: Introductionmentioning
confidence: 99%